The role of charge transfer in the formation of type i deep eutectic solvent-analogous ionic liquid mixtures - Abranches, Dinis O. (2018)
It was recently shown that tetramethylammonium chloride presented negative deviations to ideality when mixed with tetraethylammonium chloride or tetrapropylammonium chloride, leading to a strong decrease of the melting points of these salt mixtures, in a behavior akin to that observed in the formation of deep eutectic solvents. To better rationalize this unexpected melting point depression between two structurally similar compounds devoid of dominant hydrogen bonding capability, new solid–liquid equilibria data for tetramethylammonium-based systems were measured and analyzed in this work. Molecular dynamics was used to show that the strong negative deviations from ideality presented by these systems arise from a synergetic share of the chloride ions. A transfer of chloride ions seems to occur from the bigger cation in the mixture (which possesses a more disperse charge) to the smaller cation (tetramethylammonium), resembling the formation of metal–chloride complexes in type I deep eutectic solvents. This rearrangement of the charged species leads to an energetic stabilization of both components in the mixture, inducing the negative deviations to the ideality observed. The conclusions presented herein emphasize the often-neglected contribution of charge delocalization in deep eutectic solvents formation and its applicability toward the design of new ionic liquid mixtures.